2022
DOI: 10.3389/fnagi.2022.919343
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Alpha-Synuclein: Inextricable Link Underlying the Pathologic Progression of Parkinson's Disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease, with typical motor symptoms as the main clinical manifestations. At present, there are about 10 million patients with PD in the world, and its comorbidities and complications are numerous and incurable. Therefore, it is particularly important to explore the pathogenesis of PD and find possible therapeutic targets. Because the etiology of PD is complex, involving genes, environment, and aging, finding common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 206 publications
(222 reference statements)
1
14
0
Order By: Relevance
“…Our previous studies have shown that long-term hypoxia can damage nerve function and promote the transformation of α-syn into p-α-syn and its subsequent accumulation in the brain[48] [49]. In the present study, we found nerve damage and p-α-syn accumulation around the damaged area in the brain of both IS and simple hypoxia injury model mice.…”
Section: Discussionsupporting
confidence: 67%
“…Our previous studies have shown that long-term hypoxia can damage nerve function and promote the transformation of α-syn into p-α-syn and its subsequent accumulation in the brain[48] [49]. In the present study, we found nerve damage and p-α-syn accumulation around the damaged area in the brain of both IS and simple hypoxia injury model mice.…”
Section: Discussionsupporting
confidence: 67%
“…Our previous study found that hypoxia is a common factor of various pathogenic factors of PD 36 . It is a new perspective to interpret PD from the perspective of hypoxia.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have proposed that the pathogenesis of PD can be divided into three stages, which are related to triggers, facilitators, and aggravators, respectively 53 . As a common feature of various PD pathogenesis factors, 36 hypoxia may be a key mechanism in PD, which still needs further discussion. This study provides reliable evidence for subsequent studies, providing a promising research perspective for the intervention of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent WATCH-PD study used the same software analysis (BrainBaseline ™) to successfully correlate symptoms in Parkinson’s Disease patients with a similar range of movement biomarkers at sea level [10]. Hypoxia may also be a key factor in the pathogenesis of Parkinson’s Disease [28].…”
Section: Discussionmentioning
confidence: 99%